Smoking and Comorbidities in Covid-19: A Systematic Review - Nugraha, Andri; Ernawati, Ernawati; Utama, Tuti Anggriani; Rinjani, Santi (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
COVID-19 is highly contagious, causing pneumonia, respiratory failure, death, and becoming a pandemic. Patients with severe infections must be treated in the Intensive Care Unit (ICU) with a ventilator. Ventilator facilities in the ICU are limited; it must take precautions by knowing the characteristics of patients at high risk of severe disease in COVID-19, one of which was smoking or comorbidity. The purpose of this study was to assess the risk of comorbidity and smoking in COVID-19. This study used systematic review by searching for articles from the ScienceDirect and Medline databases with journals published on January 1, 2019 - March 31, 2020. The results of the study showed that there were 12 relevant articles full text in English and were analysed. The conclusion was that patients with COVID-19 who were smoking or had comorbidities were more susceptible to COVID-19 infection, more severe illness, and causing death.